Land Issues in Rural Areas: Could a Moment of Truth Ever be Reached? - Ольга Петровна Фадеева (Journal of Economic Sociology, 2010)
The paper is devoted to history and present status of land relations in rural areas of Russia. It also studies collisions of divergent interests of agricultural producers originated from the uncertainty of property rights to land and competitive struggles for the best resources. As far as full-scale market relationships for land does not exist and “virtual” joint shared ownership prevails in Russia it is reasonable to speak about the formation of local markets for land rental where the competition turns out to be among large agricultural producers and farmers and where informal agreements preventing land turnover and protecting interests of tenantry are concluded. Thus, the informal system of agreements and compromises helps to compensate for the weaknesses of formal mechanisms for land tenure. Nevertheless, the barriers to transformation of land into capital assets dramatically hinder diffusion of innovations in agriculture development.